Identifikasi Potensi Air Tanah di Pulau Katela Kabupaten Muna Barat Menggunakan Metode Geolistrik Resistivitas - La Ode Andimbara; Sawaludin Sawaludin (Jurnal Rekayasa Geofisika Indonesia, 2024)
Island Katela has a population of 957 people. Currently, the community has difficulty getting clean water. Activities to identify potential groundwater resources on Katela Island need to be carried out to solve this problem. The purpose of this research activity is to identify the subsurface of the land on Katela Island, West Muna Regency using the geoelectric resistivity method to obtain information on the potential of the groundwater layer. The main objective is to determine the existence of groundwater resources on Katela Island where the presence of groundwater is depicted in 2-dimensional (2D) and 1-dimensional (1D) subsurface resistivity cross-sectional models. The results obtained show that the structure of the subsurface layers in the survey area consists of layers of clay, sand, sandstone, limestone, salt water layers and groundwater (fresh) layers. The potential existence of a groundwater layer (fresh) is at a depth of 31.25 m at Site 1, with a resistivity value above 0.2 Ωm to 1 Ωm. This layer is thought to be a fresh water layer because above it there is a layer of clay which is impermeable so it is difficult for sea water to intrude. Based on resistivity data, at shallow depths (at the surface to a depth of 25 m) in the survey area sea water has been intruded.